PESERTA DIDIK ERA REVOLUSI INDUSTRI 4.0 VS GURU ERA REVOLUSI INDUSTRI 3.0 (PENDIDIKAN BERBASIS TEKNOLOGI: PERMASALAHAN DAN TANTANGANNYA) - Murtadho, Fathiaty (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The demands of the era of industrial revolution 4.0 in all aspects of life will be felt, one of which is in the world of education. The demand for teachers to be able to prepare and present learning using technological advances requires teachers to change their mindset and pattern of view. This is in accordance with the demands and description of teacher's tasks mandated in Law No. 4 of 2005 on Teachers and Lecturers, as well as those stated in 2013 Revised Curriculum. Teachers are also required to create learning that has the following five component components; (1) critical thinking skills, (2) having innovative creativity and abilities, (3) cooperative ability, (4) good communication skills and abilities, and (5) having high self-confidence.Will but not all of these demands This can be realized well. This is because the readiness of human resources for teachers has not been able to change the mindset and lifestyle according to the demands of the industrial revolution 4.0. Therefore there is concern that millennial era students and the industrial revolution era 4.0, will be served by teachers who do not fit the mindset with their students.